Multiplier Effects of Tourism Sector in Yogyakarta: Input-Output Analysis (Universitas Negeri Semarang, 2023)
In the Special Region of Yogyakarta (DIY), the tourism sector contributes roughly to 34% of the total output, either directly or indirectly. Because of the enormous potential of tourism in boosting the economy, the local government was encouraged to adopt plans and programs so that the tourism sector's long-term viability can influence the development of other sectors. This study aims to describe the economic multiplier effects of tourism industry operations. An examination of the input-output table of 35 sectors in the Special Region of Yogyakarta in 2015 was carried out in this study. An examination of output, income, gross value added, and labor linkage and multipliers was made from an input-output analysis. The hotel and restaurant industry, as well as air transport, is considered as the key sector in the linkage study (forward and backward linkage). The sector with the biggest employment absorption, according to the multiplier analysis, is trade.